Monitoring Application in Academic Evaluation for Web-Based Teacher Performance Assessment at SMA IT Imam Syafi'i - Okta Veza (Engineering and Technology International Journal, 2022)
The design of the Web-Based Teacher Performance Assessment Monitoring Application at SMA IT Imam Syafi'i is an application to support the performance of related agencies. Lack of data collection and the absence of supporting applications and data that are still stored in archives and computers manually. This system is designed based on website using html, css programming language and MySQL database. While the development of the research system uses the RAD (Rapid Application Development) method with the stages of requirements, workshop design, and implementation. This application serves as a method for determining the application of monitoring techniques in the academic assessment of teacher performance. With this designed system, it will be easier for agencies to monitor the academic assessment of teacher performance. And the need to make a teacher performance evaluation report.